PROJECT TECHNOLOGY IN THE INNOVATIVE SYSTEM TEACHER ACTIVITIES (Pedagogy of Higher and Secondary Education, 2022)
The essence, leading ideas of project technology and ways of its usage in teacher's innovative activities are considered in the article.